2019
DOI: 10.1007/978-3-030-11899-0
|View full text |Cite
|
Sign up to set email alerts
|

The Biopsychosocial Model of Health and Disease

Abstract: use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license and indicate if changes were made. The images or other third party material in this book are included in the book's Creative Commons license, unless indicated otherwise in a credit line to the material. If material is not included in the book's Creative Commons license and your intended use is not permitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(87 citation statements)
references
References 1 publication
3
83
0
1
Order By: Relevance
“…Our study is guided by Engel’s biopsychosocial risk factor model of disease that explains health outcomes as a result of an interaction between biological, social and psychological risk factors [ 27 ]. These factors can either predispose, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Our study is guided by Engel’s biopsychosocial risk factor model of disease that explains health outcomes as a result of an interaction between biological, social and psychological risk factors [ 27 ]. These factors can either predispose, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted in Australia demonstrated the importance of including psychological, biological and sociocultural factors in models of body image and eating concerns in young female adolescents (Rodgers et al, 2014). Mental health complications of medical conditions is an increasingly recognised issue with implications on the quality of life (Bolton and Gillett, 2019). Considering the interaction of psychological, biological, socio-cultural factors, there is need for diagnosis and management of illness in lowmiddle income countries in Africa to consider incorporating psychological services into physical healthcare pathways.…”
Section: Mental Health and Chronic Illnessmentioning
confidence: 99%
“…These findings support the view that understanding psychopathy and antisocial behavior requires more fine-grained insights into the cognitive mechanisms underlying aberrant behaviors, which can potentially lead to more targeted therapies to remedy the impairments. In this way, the spirit of the RDoC project can be extended to include computational considerations when devising new classifications and measures for doing research (for further extensions of RDoC, see Bolton & Gillett, 2019).…”
Section: A Biocognitive Approach To Antisocial Behaviormentioning
confidence: 99%
“…Among the problematic and imprecise concepts, they included terms such as behavioral health conditions, mental disorders , or mental health conditions because they give the impression that there is an autonomous mental substance to which mental problems pertain disconnected from its physical underpinnings. All parties to this debate seem to agree that mind and body are not really different substances and that biological factors have a role in psychiatric research (Bolton & Gillett, 2019; Borsboom et al, 2019). Nonetheless, there is a tendency to overemphasize observable behavior, subjective reports, and relations between symptoms of mental disorders that creates an artificial wedge between psychiatry and the rest of medicine (Insel & Cuthbert, 2015; White, Rickards, & Zeman, 2012).…”
Section: Biocognitive Classification Without Reductionismmentioning
confidence: 99%